Job shadowing adults' non-formal education programme through social-emotional learning - Margeviča-Grinberga, Ieva; Kalēja, Aija (Frontiers in Sociology, 2025)
This study explores the impact of a job shadowing non-formal education program, integrated with social and emotional learning (SEL), on adult professional development and career planning. The program engaged adults from diverse professional backgrounds, providing them with structured opportunities to observe and interact with experienced professionals in real workplace environments. A mixed-methods approach was employed, combining self-assessment questionnaires, interviews, and reflective journals to capture both quantitative and qualitative dimensions of participant experience. Findings indicate that participation in SEL-based job shadowing fosters the development of professional identity, emotional intelligence, and adaptability among adult learners. Participants reported increased self-confidence, enhanced workplace communication, and greater clarity in career direction. The program also supported the acquisition of practical skills and encouraged ongoing professional learning, with many participants expressing motivation to pursue further education or training. The results highlight the value of integrating SEL principles into job shadowing as a non-formal education programme, demonstrating its effectiveness in supporting career transitions, lifelong learning, and workforce readiness in a rapidly changing labor market. These insights underscore the importance of designing job shadowing as a non-formal education programme that not only addresses skill development but also promotes emotional and social competencies essential for sustainable professional growth. This study contributes to the theoretical understanding of how experiential, SEL-driven job shadowing can facilitate holistic adult development and provides practical recommendations for educators, policymakers, and employers seeking to enhance the relevance and impact of non-formal learning programs for adults.